Developmental characteristics in children with Down syndrome from ages 5 to 12 in Bogota, Colombia (2019)
Introduction: Cognitive processing and learning skills are widely variable amongst individuals with Down syndrome (DS). The achievement of developmental milestones behaves in a different way than it does in children with typically development. Thus, the characterization and understanding of children with DS is important to elaborate intervention strategies and follow-up programs. Objectives: To establish a cognitive developmental profile in children with DS. Materials and Methods: Observational, descriptive, cross-sec- tional study of 93 children between the ages of 5 and 12, among three health institutions in Bogota (Colombia). For assessment, the Battelle Developmental Inventory (BDI-2) and the Child Neuropsychological Evaluation (ENI) were used. The institutional review board approved the study. Results: Developmental quotients were below than normative data for typically developed children in all evaluated domains. The neurocognitive profiles exhibited a discretely, age dependent, ascendant tendency, the areas that were more strongly developed were adaptive behavior, social skills and gross motor control. Conclusions: The obtained results allowed to design a curve that comprehensively shows the skills in learning that children with DS show. Furthermore, it showed the specific areas in which children perform in a more efficient manner, and those in which they have major setbacks or pitfalls. Namely, gross motor control and social skills, are areas in which children with DS have significant skills, whilst communication, language and cognitive processing are less developed. ©2019 Ediciones Mayo.S.A. All rights reserved.